Penguatan Peran Pemolisian Masyarakat Dalam Mewujudkan Stabilitas Kamtibmas Bagi Pembangunan Nasional Tahun 2022: Penguatan Peran Pemolisian Masyarakat Dalam Mewujudkan Stabilitas Kamtibmas Bagi Pembangunan Nasional Tahun 2022 - Azis Saputra (Pusat Penelitian dan Pengembangan Polri, 2023)
The need and importance of realizing Kamtibmas stability as mandated by the constitution through Law No. 2 of 2002 that in realizing the synergy of public relations and the Police, the Police are tasked with fostering the community to increase community participation, community legal awareness and citizen obedience to laws and regulations. The National Police, through Community Policing efforts, has inflamed the internal ranks of the Police and socialized it to the public. Until now, only 38,477 Bhabinkamtibmas have been held, around 46.15%. Fulfillment of the 53.85% shortfall can be fulfilled if a Polmas officer can be assigned. In order to realize the achievement of increasing the Kamtibmas Index and strengthening Harkamtibmas, the National Police Research and Development Center conducted research on Strengthening the Role of Community Policing to Realize Kamtibmas Stability for National Development using a qualitative approach and secondary data collection. Respondents and informants consisted of internal and external police officers. The Internal Police consists of Polda Officers, Polres, and related Polres members. Externally, the National Police are Community Leaders, Religious Leaders, Traditional Leaders, Youth Leaders, Government Agencies (Kesbangpol), Village/Lurah Heads, Babinsa, FKPM, Pokdar Kamtibmas, NGOs/Ormas. The results of the study stated that: The implementation of Polmas duties is still understood as Bhabinkamtibmas officers so it is necessary to socialize Perpol No. 1 of 2021 concerning Polmas; The coordination of the Binmas function with other technical functions has not been optimally implemented because there has not been cross-functional knowledge transfer; Cross-functional and stakeholder coordination activities need to be optimized; Development of the ability to detect, identify and solve security and order problems for the community must be carried out on an ongoing basis; Polmas implementation through partnerships is implemented but needs to be optimized; Understanding of the partnership between Polri and the community through Polmas is still low; The partnership between the Police and the community in the implementation of Community Police has been carried out, but through institutions outside the FKPM.